Uroradiological screening for upper and lower urinary tract anomalies in patients with hypospadias: a systematic literature review. Issue 1 (19th July 2012) - Chariatte, Vincent; Ramseyer, Pascal; Cachat, François
Abstract : Introduction: Hypospadias is associated with anomalies of the urinary tract, but the exact prevalence and significance of these anomalies are still controversial. Objectives: To assess the percentage of patients with hypospadias and associated urological anomalies, either requiring or not requiring medical or surgical attention. Material and methods: We searched several databases using the following Mesh terms: hypospadias AND urination, ultrasonography, urinary tract/abnormalities, urinary bladder/radiography, ureteral obstruction, hydronephrosis or vesico-ureteral reflux. Type of uroradiological studies performed, type of urological anomalies, medical or surgical interventions, number of patients available, enrolled and undergoing uroradiological studies and number of patients with abnormal uroradiological exams were recorded. Results: We found 24 studies. Four studies included 100% of available patients. In the other ones, the percentage of patients undergoing uroradiological screening varied from 12 to 82%. Frequency of anomalies varied from 0 to 56%. The most common anomalies were kidney position anomalies, vesico-ureteral reflux and hydronephrosis. Conclusions: The data published about screening patients with hypospadias for associated anomalies of their urinary tract are of poor quality. The clinical significance of the anomalies found is difficult to evaluate. We found no relationship between the severity of the hypospadias and associated anomalies of the upper or lower urinary tract.